Confinement theorem for high-current plasma lens - Goncharov, A.A.; Maslov, V.I.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2000)
The theorem about a fraction of magnetized electrons, which could reach the cylindrical wall, is generalized for the case of collisionless plasma lens for focusing of ion beams. Long electron column is considered. The electrons are partly noncompensated by ions. It is shown from the conservation of angular momentum that if the radius of electron column is small in comparison with the distance from the column to the wall then the only small fraction of electrons from the column could reach the wall.